The Effects of Increased Glucose Level and Glycolysis on SARS CoV-2 Infection - Ozlem Zurnaci, Fatma; Guzel, Mustafa (Mini Reviews in Medicinal Chemistry, 2022)
COVID-19 has entered our lives as an infection with high mortality rates. Although the vaccination process has provided benefits, the death toll remains frightening worldwide. Therefore, drugs and combined therapies that can be used against COVID-19 infection are still being investigated. Most of these antiviral medications are investigational drug candidates that are still in clinical trials. In this context, holistic and different approaches for the treatment of COVID-19, including prophylactic use of natural medicines, are under investigation and may offer potential treatment options due to the fact that this is still an unmet medical need of the world. Thus, inhibiting the increased glycolysis in COVID-19 infection with glycolysis inhibitors may be beneficial for patient survival. This short review highlights the potential benefits of glycolysis inhibition as well as controlling the elevated glucose levels in patients with COVID-19.
Keywords: glycolysis inhibition